A teaching note on Cook's distance - a guideline - McDonald, Barry (Massey University, 2002)
Cook’s Distance (Di) is used for assessing influence in regression models. The usual criterion is that a point is influential if Di exceeds the median of the Fp,n-p distribution, where p is the number of regression parameters. The practice developed here at Massey Albany is to teach the guideline Di>0.7 for p=2, Di> 0.8 for p=3, Di> 0.85 for p>3, where n≥15. It is not known if this guideline is used elsewhere.
Keywords: Cook's Distance; Regression models